STUDY ON CONSUMER ACCEPTANCE OF CATFISH (Pangasius hypophthalmus) GRILLED FISH CAKE WITH DIFFERENT PROCESSING - Mayer Titus Siburian; Dewita Dewita; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT                The purpose of this study was to determine consumer acceptance of catfish (Pangasius hypophthalmus) grilled fish cake with different processing. The research method used was the experimental method of making the grilled fish cake with different processing, namely X1 (fried) and X2 (grilled). Then a comparative study was conducted to compare treatment using the t-test. Based on the results of research from organoleptic assessment, the catfish grilled fish cake X2 was significantly different from the catfish grilled fish cake X1 at a 95% confidence level. Viewed from the aspect of appearance X1 7.19 X2 7.44, taste X1 6.93 X2 7.46, texture X1 6.92 X2 7.13 and aroma X1 7.04 X2 7.34 in the catfish grilled fish cake X2 treatment was higher than catfish grilled fish cake X1 treatment. The processing of catfish grilled fish cake with grilled processing was most preferred by consumer acceptance with characteristics of appearance quite brilliant without mucus), taste (specific of grilled fish cake), texture (quite dense and elastic) and aroma (specific of grilled fish cake) with chemical value of ash, fat, protein, moisture, and carbohydrate content was 1.43%, 4.26%, 15.34%, 22.68%, and 53.00%, respectively. Key Words: catfish, grilled fish cake, fried, grilled